Cultural Transformation in Indonesian Urban Society: A Case Study of The Millennial Generation - Haniah, St.; Firdaus, Firdaus; Amin, Sulvahrul (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study highlights the cultural transformation of the millennial generation in urban Indonesia, influenced by technological advances, social media and globalisation. Despite maintaining a unique cultural identity, this generation faces challenges in maintaining a balance between modernity and cultural heritage. The implications include policy development and cultural maintenance in the future. Previous research has examined the influence of globalisation on young people, but this study provides a specific focus on millennials' responses to foreign culture and behavioural changes, making a valuable contribution to previous understanding.